Color in Context: Three Angles on Contemporary Colorism. Issue 3 (July 2021) - strmic-pawl, hephzibah v.; Gonlin, Vanessa; Garner, Steve
Colorism is a form of discrimination based on skin tone wherein people with light(er) complexions are advantaged over those with dark(er) ones. In this review, we define key terms, explore colorism as an individual and structural phenomenon, and identify some predominant themes in the existing scholarship on colorism. We review three case studies of contemporary uses and ramifications of colorism in order to encourage scholars to engage with this important field. These case studies are skin tone's impact on U.S. politics, "transraciality, " the appropriation of skin tone, and finally, the global skin lightening industry. While the first two are mostly focused on the United States, the third enables an appreciation of the global dynamics of colorism, and links back to the national and regional contextual politics of skin tone.